Sustaining Robust Growth, Mitigating Risks and Deepening Reforms : Lao PDR Economic Monitor, May 2012 - World Bank (World Bank, Vientiane, 2013)
With development soaring in construction, manufacturing, mining and services, Lao PDR's economic outlook in 2012 is positive. As the driving force behind the domestic economy, these sectors are anticipated to drive a projected growth of 8.3 percent by year-end. To begin, higher wholesale and trading, tourism as well as transport and telecommunications will impact the service sector this year. A construction boom is also on the horizon supported by the preparation for the 9th Asia-Europe Meeting (ASEM) in Vientiane Capital. With this said, construction will support the manufacturing sector with the additional demand for cement and construction materials. Food and beverages will also expand in response to sustained domestic demand. Additionally, Phu Bia mining company's upgrade of existing copper and new gold and silver projects will generate more output from the mining sector. On the other hand, the power sector will contribute less in comparison to last year, despite the operation of Nam Ngum 5 hydropower project. In the mean time, agricultural output is expected to rebound after the adverse impacts of 2011's floods. Despite this robust growth, the medium-term outlook remains subject to uncertainty in external markets. In 2011, the National Assembly revised and approved the general tax law introducing public finance to a transparent, turnover based presumptive tax regime for businesses with a turnover below the Value-Added Tax (VAT) registration threshold. In effect, this law eliminated minimum business tax. Finally, the implementation of the 'one-stop' service (as stipulated on the enterprise law and the new investment promotion law) commenced in October 2011.